2012
DOI: 10.1371/journal.pone.0044045
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Induction by Exosomes from Immature Dendritic Cells and Rapamycin in a Mouse Cardiac Allograft Model

Abstract: BackgroundDendritic cells (DCs) release bioactive exosomes that play an important role in immune regulation. Because they express low levels of class I major histocompatibility complex (MHC) and co-stimulatory molecules, exosomes derived from donor immature DCs (imDex) prolong allograft survival by inhibiting T-cell activation. However, this effect is limited and does not induce immunological tolerance when imDex are administered alone. Thus, we tested the effect of combined treatment with donor imDex and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 34 publications
5
75
0
Order By: Relevance
“…Biologically derived nanoparticles are an emerging subset of lipid nanoparticles that have been shown to effectively deliver a wide range of functional biomolecules, evade or dampen immune responses, and accumulate in tumors (2)(3)(4). In particular, exosomes, which are endosomally derived secreted vesicles, have shown great promise as therapeutic delivery vehicles (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biologically derived nanoparticles are an emerging subset of lipid nanoparticles that have been shown to effectively deliver a wide range of functional biomolecules, evade or dampen immune responses, and accumulate in tumors (2)(3)(4). In particular, exosomes, which are endosomally derived secreted vesicles, have shown great promise as therapeutic delivery vehicles (5,6).…”
mentioning
confidence: 99%
“…In contrast, displaying targeting ligands on exosomes is relatively simple because peptide ligands can be genetically fused to the extra-exosomal termini of exosomal membrane proteins. This strategy has been applied to target exosome uptake by neurons by fusing a rabies viral glycoprotein (RVG) 3 peptide to the N terminus of lysosomal associated membrane protein 2b (Lamp2b) (7). Such a fusion resulted in RVG peptide being displayed on the surface of exosomes, leading to exosome uptake via the nicotinic acetylcholine receptor.…”
mentioning
confidence: 99%
“…Importantly, exosomes from a variety of cell populations can mediate either immune activation or immune suppression based on the individual immunological microenvironment. [34][35][36][37] In autoimmunity, it has also been suggested that exosomes play a role in the chronic inflammatory response and that the cellular origin of exosomes will differentially influence the immune response in autoimmune disease. 6,38,39 Our data are important because they emphasize that co-stimulatory molecules play a pivotal role in APC-mediated immune responses, particularly T-cell activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Immature DCs release exosomes more vigorously than mature DCs [22,23] . Immature DC exosomes exhibit a potent role in Treg cell activation [23,24] , suggesting maintenance of homeostasis by suppressing autoimmune reactions and excessive inflammations. Whereas, mature DCs release exosomes to facilitate tumoricidal immune reactions.…”
Section: Exosomes and Immune Regulationmentioning
confidence: 99%